DAMPAK MISI DAN PENGINJILAN DI BATAK TOBA - Chaliya Elisabet T - (STT Bethel The Way, 2021)
The research objective describes the community in Batak Toba before, after the entry of mission and evangelism, as well as the process of entering Christianity. The results showed that mission and evangelism were very important for the Toba Batak people to believe in Christ, changing the concept of belief in the animist ancestors into believing in the Lord Jesus, bringing developments in economics, education and health. This research was conducted using descriptive qualitative methods. The researcher concludes that mission and evangelism comes from the heart of God for all nations, so that many people will know and believe in Christ, so that they will not perish but may gain eternal life Keywords : Mission and Evangelism, Batak Toba